Domestic Private Sector Participation in Peru : Sanitation Markets at the Bottom of the Pyramid--A Win-Win Scenario for Government, the Private Sector, and Communities - World Bank (Washington, DC, 2014)
Peru has benefitted from macroeconomic stability and growth in the last few years. At the same time, it also presents important contradictions in terms of unresolved access to basic sanitation. This is characterized by: a) an on-going gap that reflects the high levels of inequity between rural and urban coverage, b) unused services and low levels of customer satisfaction with current sanitation solutions, and c) unsustainable and inefficient public investments. Despite of the important infrastructure investments of the last 20 years, significant gaps remain, as well as the need to address quality and sustainable sanitation service. Moreover, it has not impacted the improvement of health and environment-related indicators. According to the National Statistics Institute, while national sanitation coverage has increased by 20 percent (1993-2007), in the same period the percentage of prevalence of chronic malnutrition in children under five years old has decreased by 9 percent and that of diarrhea by only 5 percent.